CORRUPTOR FIGHT BACK: IDENTIFYING THE CORRUPTION ERADICATION COMMISSION'S ENEMY IN ERADICATING CORRUPTION IN INDONESIA - Muttaqin, Labib (PEOPLE: International Journal of Social Sciences, 2020)
The Corruption Eradication Commission of the Republic of Indonesia (CEC) is a state institution established with the aim of improving the effectiveness of efforts to eradicate corruption. With a clear juridical foundation and real achievement, the CEC is considered successful in meeting public expectations in eradicating corruption in Indonesia. Even so, the CEC's corruption eradication agenda experienced many obstacles from those who were against corruption eradication. The parties are always trying to weaken the CEC institution even there are also efforts to dissolve the CEC. Various attempts to weaken the CEC are called corruptor fight back. But unfortunately, the incessant corruptors fight back are not matched by the CEC's readiness in dealing with the fight back. Not yet identified the pattern of corruptor fight back is one indication of the weakness of the CEC in the face of the corruptor fight back. Therefore, there are three objectives of this study namely; First, learn the forms of the corruptor fight back. Second, read the workings of the corruptor fight back. Third, determine the ideal design and strategy to prevent and fight any corruptors fight back.